Adsorção de Mn (II) e Zn (II) em soluções aquosas usando perlita expandida revestida com quitosana - Santos, Elisama Vieira dos (2011)
In this work, chitosan was used as a coating of pure perlite in order to increase the accessibility of the groups OH- e NH2+the adsorptionof ions Mn2+ e Zn2+.The characterization results of the expanded perlite classified as microporous and whose surface area 3,176 m2 g-1after the change resulted in 4,664 m2g-1.From the thermogravimetry(TG) it was found that the percentage of coating was34,3%.The infrared analysis can prove the presence of groups Si-OH, Si-O e Al-O-Siresulting from the perlite and C=O, NH2and OH characterization of chitosan. The experiments on experiments on the adsorption of Mn and Zn were performed in the concentration range of10 a 50 mgL-1and the adsorption capacity inpH 5,8 e 5,2 was 19,49 and 23,09 mgg-1to 25 oC,respectively.The adsorption data were best fitted to Langmuir adsorption model to Langmuir adsorption model for both metalionsisindicative of monolayer adsorption. The kinetics of adsorption were calculated from the equation of Lagergren fitting the model pseudo-second-order for all initial concentrations, suggesting that adsorption of ions Mn2+ and Zn2+ follows the kinetics of pseudo-second-order and whose constant Speedk2(g/mg.min) are 0,105 e 3,98 and capacity and maximum removal qe 4,326 e 3,348,respectively.In this study we used a square wave voltammetry cathodic stripping voltammetry to quantify the adsorbed ions, and the working electrode glassy carbon, reference electrode silver / silver chloride and a platinum auxiliary electrode. The attainment of the peaks corresponding to ions Mn2+ and Zn2+ was evaluated in and electrochemical cell with a capacity of 30 mL using a buffer system (Na2HPO4/NaH2PO4)at pH 4 and was adjusted with solutionsH3PO4 0,1molL-1and NaOH 0,1 molL-1and addition of the analyte has been a cathodic peak in- 0,873 Vand detection limit of2,55x10-6molL-1para Zn.The dough used for obtaining the adsorption isotherm was 150 mg and reached in 120 min time of equilibrium for both metal ions.The maximum adsorption for 120 min with Mn concentration 20 mgL-1 and Zn 10 mgL-1,was91, 09 e 94, 34%, respectively